Sex begins in the kitchen eaudiobook Creating intimacy to make your marriage sizzle. - Leman, Kevin (christianaudio, 2013)
Sex Begins in the Kitchen shows couples everywhere how to bring more passion into their marriages. Best-selling author Dr. Kevin Leman explains how sexual intimacy is an expression of the care a couple shows each other in all areas of life—in communicating, sharing thoughts and feelings, and even in helping out around the house. With insightful—and often hilarious—examples, Dr. Leman shows couples how to create new joy and excitement in their relationships and make their marriages more satisfying both emotionally and physically.